2019
DOI: 10.3390/genes10090640
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Radiation Therapy on Neural Stem Cells

Abstract: Brain and nervous system cancers in children represent the second most common neoplasia after leukemia. Radiotherapy plays a significant role in cancer treatment; however, the use of such therapy is not without devastating side effects. The impact of radiation-induced damage to the brain is multifactorial, but the damage to neural stem cell populations seems to play a key role. The brain contains pools of regenerative neural stem cells that reside in specialized neurogenic niches and can generate new neurons. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 142 publications
(179 reference statements)
0
28
0
Order By: Relevance
“…External beam radiation therapy is an essential part of treatment of brain tumors and brain metastases [2,3]. Radiation techniques were initially based on 2D radiation therapy by means of rectangular fields built on basic X-ray imaging for field placement verification.…”
Section: Improvement Of Techniques In Radiation Therapymentioning
confidence: 99%
See 2 more Smart Citations
“…External beam radiation therapy is an essential part of treatment of brain tumors and brain metastases [2,3]. Radiation techniques were initially based on 2D radiation therapy by means of rectangular fields built on basic X-ray imaging for field placement verification.…”
Section: Improvement Of Techniques In Radiation Therapymentioning
confidence: 99%
“…In 2018, the prevalence of central nervous system (CNS) tumors was estimated in 3.5 per 100,000 men and women (all ages) [3]. Chemotherapy for brain tumors is generally restricted by delivery obstacles associated with the blood-brain barrier (BBB) that precludes achieving sufficient concentrations of chemotherapeutic agents in the tumors [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the effects of radiotherapy on neural stem cells are also different from its effects on glioma stem cells. Radiotherapy induces acute apoptosis in dividing cells and reduces the pool of mitotic neural stem cells, mainly the activated neural stem cells and the neural progenitor cells [72]. Glioma stem cells are, however, resistant to radiation therapy [15].…”
Section: Resultsmentioning
confidence: 99%
“…However, radiotherapy may cause radiation induced myelopathy especially used for spine bone metastasis [5]. Recently, researches have demonstrated that radiation treatment damaged the functions of neural stem cell (NSC), which was one of the key pathogenesis of radiation induced myelopathy [6]. However, the detailed mechanism is largely unclear.…”
Section: Introductionmentioning
confidence: 99%